2012
DOI: 10.1177/1470320312452768
|View full text |Cite
|
Sign up to set email alerts
|

Association of angiotensin-converting enzyme gene insertion/deletion polymorphism with polycystic ovary syndrome: a meta-analysis

Abstract: Introduction Angiotensin converting enzyme (ACE) is a renal enzyme catalyzing the conversion of angiotensin 1 to angiotensin 2. This, results in production of the aldosterone resulting in natrium retention and potassium excretion. ACE gene has 3 polymorphic genotypes of II, DI and DD. It has been observed in several studies and meta-analyses that patients with DD genotype are more at risk of renal and cardiovascular diseases. It seems that these effects could be due to hyperactivity of ACE gene in such patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Several studies reported no contribution of this polymorphism in susceptibility to PCOS, however, few studies did find a relationship with insulin resistance, hyperandrogenism and aggravated clinical manifestations of PCOS [16][17][18]. A recent meta-analysis by Jia Hongxia et al (2012) reported a significant relation between this polymorphism and PCOS risk in Caucasians but produced a null result for Asians [15]. Since no studies were reported from India, the present study was carried out in South Indian women in order to establish the role of ACE I/D polymorphism in susceptibility to PCOS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies reported no contribution of this polymorphism in susceptibility to PCOS, however, few studies did find a relationship with insulin resistance, hyperandrogenism and aggravated clinical manifestations of PCOS [16][17][18]. A recent meta-analysis by Jia Hongxia et al (2012) reported a significant relation between this polymorphism and PCOS risk in Caucasians but produced a null result for Asians [15]. Since no studies were reported from India, the present study was carried out in South Indian women in order to establish the role of ACE I/D polymorphism in susceptibility to PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…To date, most of the studies conducted on PCOS patients from various ethnic groups differ in their reports [15]. Controversial reports of this polymorphism with the clinical manifestations such as insulin resistance and testosterone levels among the PCOS patients were also reported [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic studies further demonstrate that polymorphisms in Ace1 are related to the risk factors for PCOS. Jia and his team proposed that Ace1 insertion/deletion (I/D) polymorphisms are associated with an increased risk for PCOS [81]. The D allele, which is found in approximately 55% of the population, is associated with increased ACE1 activity [82].…”
Section: Sterility Of Metsmentioning
confidence: 99%
“…The meta-analysis performed by Jia et al 13 in 2013 showed no association of polymorphisms with PCOS in the general population. Only after stratification in ethnicities, it was concluded that the polymorphism is associated with the disease in Caucasian women, but it is not related in Asian women.…”
Section: Discussionmentioning
confidence: 97%
“…A meta-analysis involving six studies with 1,451 patients and 773 controls suggested that the polymorphism is associated with the risk of developing PCOS in Caucasian women. 13 In addition, there are no studies on this polymorphism and PCOS in Brazilian women. In view of the above, this study aimed to determine the frequency of the insertion (I)/deletion (D) polymorphism of the ACE gene (rs1799752) in patients with PCOS and to compare it with a control population in order to verify the association of this polymorphism with the syndrome.…”
Section: Introductionmentioning
confidence: 99%